Marine Technology Innovation and Sustainable Economic Development - Rizka Dwi Puspitasari; Iqbal (Journal of Economic Growth and Development Review, 2026)
Marine technology innovation plays a crucial role in supporting sustainable economic development, particularly in coastal and maritime regions. Advances in marine engineering, offshore structures, renewable ocean energy, and digital marine technologies have contributed to increased productivity, efficiency, and resilience within the maritime sector. This study examines the relationship between marine technology innovation and sustainable economic development by highlighting the roles of human capital, technological advancement, and entrepreneurial activities in the marine industry. Using a qualitative literature-based approach, this study analyzes academic publications, policy reports, and relevant case studies related to marine technology and the blue economy. The findings indicate that marine technology innovation enhances economic growth by optimizing the use of marine resources, reducing environmental impacts, and creating new opportunities for maritime entrepreneurship and employment. Furthermore, sustainable marine development depends on the integration of technological innovation with skilled human resources and supportive institutional frameworks. This study emphasizes the importance of marine technology innovation as a strategic driver for achieving sustainable and inclusive economic development in the maritime sector.